Factors Affecting Honey Bee Population in Western Himalaya of Uttarakhand: An Observational Study - Parveen, Nagma; Kumar, Kulbhushan; Miglani, Rashi; Kumar, Ankit; Siddiqui, Uzma; Rawat, Gaurav; Bisht, Satpal Singh (Asian Journal of Biological and Life Sciences)
Insect pollinators, especially honey bees, are an essential biotic factor in the reproductive success of plants that rely on insects for pollination. Their extinction would endanger food production and sustainable biodiversity. Climate change, habitat destruction, fragmentation, the prevalence of diseases, parasites, insufficient nutrition, extensive agricultural practices and invasion by foreign and predatory species contribute to the decline of the honey bee population. The present study aims to observe and document the factors affecting the population of honey bees in the study area. Thus, a comprehensive survey of 59 modern and 42 traditional apiaries in the Nainital district of Uttarakhand, India, was conducted. In the present study, the most common nuisances of honeybees were insects, followed by avian fauna and arachnids. Apart from insects and arachnids, four bird species were nesting and roaming around beehives. Few insects and reptiles belonging to the non-pest category were also spotted infesting the hives in the study sites. It has been observed that these factors negatively affect the bee population. Managing these factors is crucial in conserving the native and captive bees to sustain the environment.
Keywords: Honey Bee; Parasites; Pests; Population; Predators; Western Himalaya